2018
DOI: 10.33837/msj.v1i3.106
|View full text |Cite
|
Sign up to set email alerts
|

Blind Source Separation by Multiresolution Analysis using AMUSE Algorithm

Abstract: Algorithms for blind source separation have been extensively studied in the last years. This paper proposes the use of multiresolution analysis in three decomposition levels of the wavelet transform, such as a preprocessing step, and the AMUSE algorithm to separate the source signals in distinct levels of resolution. Results show that there is an improvement in the estimation of the signals and in the mixing matrix even in noisy environment if compared to the use of AMUSE only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…In 2018, Oliveira et al proposed the use of multi-resolution analysis in the three resolution ranks of the wavelet transform, and then separated the source signal using the AMUSE algorithm with different resolution ranks. The results were better than those obtained when using the original AMUSE method alone to estimate the signal [24]. In 2019, Chua and Klejin proposed a low-delay method for BSS.…”
Section: Related Workmentioning
confidence: 89%
“…In 2018, Oliveira et al proposed the use of multi-resolution analysis in the three resolution ranks of the wavelet transform, and then separated the source signal using the AMUSE algorithm with different resolution ranks. The results were better than those obtained when using the original AMUSE method alone to estimate the signal [24]. In 2019, Chua and Klejin proposed a low-delay method for BSS.…”
Section: Related Workmentioning
confidence: 89%
“…classical approach, the spatial filtering [9] and decomposition technique such as wavelet filter Bank approach and Empirical Mode decomposition [13], [26] approach has also been used to a large extend . Furthermore, blind source separation (BSS) [10][11][12] is another efficient and extensively used technique to minimize the artifacts and to separate the source signal from the recorded EEG signal…”
Section: Eeg Signalmentioning
confidence: 99%
“…After the literature survey, it has been found that various spatial filtering has been employed before the feature extraction from the multichannel SSVEP BCI system.The features extraction from the multichannel recordings directly influences the detection accuracy because the multichannel EEG signals are correlated [8]. Blind source separation (BSS) is an advanced signal processing method applied to get the independent sources mixed at the sensor point or decorrelate the recorded EEG signal [21][22][23]. The performance of BSS, along with CCA, is a new method for detecting SSVEP from the multichannel EEG signals.…”
Section: Eeg Signalmentioning
confidence: 99%
See 2 more Smart Citations